Unravelling theory: Strategic (non-) disclosure of online ratings - David Butler; Daniel Read (Games, 2021)
This paper investigates disclosure by testing if the game theoretic predictions of unravelling theory are borne out in a heretofore unstudied market. We analyse TripAdvisor disclosures from hoteliers across 22 locations (N = 4357). Contrary to theoretical predictions, we find that disclosure decreases linearly with TripAdvisor ratings. We find the same pattern of disclosure occurs when consumers know the information provider has information to disclose, and when they do not. We also find evidence suggesting the most elite hotels may disclose less. We provide practical as well as theoretical implications.
Keywords: 330; disclosure; TripAdvisor; unravelling of information